(untitled) (Journal of Hama University, 2024)
The aim of the research is to study the development of production costs per hectare of citrus at the national level during the period (2011-2020) and to determine the optimal size of production that achieves economic efficiency through standard analysis of the functions of production costs per kilogram of citrus fruits during the studied period. The research was implemented at the level of the Syrian Arab Republic, depending on the annual agricultural statistical collections during the period (2011-2020), and using the descriptive analytical approach in studying the development of production costs during the studied period and estimating the relative importance of each item by using tables, percentages, and indices. Using the standard analytical approach by comparing standard models (linear, logarithmic, exponential, and cubic) to explain the relationship between the amount of output as an independent variable and the amount of production costs as a dependent variable. The research results showed that the cost of one kilogram of citrus reached its highest value in 2020 at about 318.10 SP / kg, with a record number of 3109.48% compared to the year 2011, an increase of 3009.48%. The costs of production requirements occupied about 42.31% of the total costs for the year 2020. The costs of agricultural operations accounted for 26.87% of the total costs, due to the needs of the citrus tree for care operations, especially breeding and pruning operations, which constituted the highest percentage in terms of costs of agricultural operations, in addition to harvesting, due to its reliance on high-paid labor. The results of the comparison between the standard models showed that the best model that expresses the relationship between production as an independent variable and costs as a dependent variable is the logarithmic model.